Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/hed.25055
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery for oropharyngeal carcinoma: Surgical margins and oncologic outcomes

Abstract: The need to take ≥2 margins to achieve resection portends an increased risk of locoregional recurrence and death due to disease in oropharyngeal SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 26 publications
8
78
4
1
Order By: Relevance
“…Pooled data from three clinical trials in a study by Weinstein et al yielded a PMR of 3.8% for OP tumors of all classifications, and a retrospective review of 11 academic institutions revealed a rate of 9.9% . Two single‐institution studies, by Moore et al and Persky et al, reported rates of 2% and 10%, respectively, for T1 and T2 tumors . These rates are lower than the PMRs of academic facilities in this study, even when limited to low‐classification tumors (13.9%).…”
Section: Discussioncontrasting
confidence: 56%
“…Pooled data from three clinical trials in a study by Weinstein et al yielded a PMR of 3.8% for OP tumors of all classifications, and a retrospective review of 11 academic institutions revealed a rate of 9.9% . Two single‐institution studies, by Moore et al and Persky et al, reported rates of 2% and 10%, respectively, for T1 and T2 tumors . These rates are lower than the PMRs of academic facilities in this study, even when limited to low‐classification tumors (13.9%).…”
Section: Discussioncontrasting
confidence: 56%
“…We found that patients 70 years or older have similar 3‐year disease‐specific oncologic outcomes (DSS, 94.3%; DFS, 79.3%) compared to published series analyzing younger cohorts . As expected, OS (81.5%) was lower than the 83%‐90% typically reported for HPV‐associated OPSCC, secondary to 21.3% dying of unrelated causes . Our analysis of these data demonstrated that elderly adults with HPV‐associated OPSCC could be subcategorized into three groups, allowing us to describe a clinically relevant decrement in 3‐year OS from 100% to 54% with rising age, ACE‐27 comorbidity score, and cT stage.…”
Section: Discussionsupporting
confidence: 70%
“…Lörincz et al examined outcomes of 50 patients who underwent TORS and reported 2‐year disease‐free and recurrence‐free survival rates at 88% and 80%, respectively . Similarly, Moore et al, in a recent large case series of 314 TORS patients, found a 3‐year overall survival rate of 91% . The large survival may be attributed to their ability to achieve negative margins in 98% of their cases.…”
Section: Introductionmentioning
confidence: 99%
“…The large survival may be attributed to their ability to achieve negative margins in 98% of their cases. In fact, they found that repeated attempts to secure negative margins were independently associated with death . Understanding whether TORS helps facilitate the achievement of negative margins is important in understanding its clinical impact and future role in OPSCC management.…”
Section: Introductionmentioning
confidence: 99%